Prediction of Scapular Dyskinesis through Strength and Range of Motion of Shoulder Joint Rotation in Competitive Boxers - Soroush Momenpour; Seyed Hosein Hoseini; Hasan Daneshmandi (Shahid Beheshti University of Medical Sciences, 2022)
Background and Aims This study investigated the relationship between shoulder rotation Range of Motion (ROM), shoulder rotation strength, and sports history with scapular dyskinesia in competitive boxers. Methods The present study was a descriptive correlational study performed on 60 male boxers (age: 24/01±3/90 years; weight: 74/61±6/73 kg; height: 176/97±6/06 cm; and sports history: 5/16±1/84 years) in Guilan. Scapular dyskinesia by lateral scapular slide test, shoulder rotation ROM using a manual goniometer, and shoulder rotation strength using a manual dynamometer were measured. Data were analyzed by Pearson and Spearman correlations and multiple regression analysis. Results There were significant correlations between sports history (p= 0.001; r=0.589), shoulder internal rotation ROM (p=0.040; r=-0.255), shoulder external rotation ROM (p=0.001; r=0.486), shoulder internal rotation strength (p= 0.009; r=0.334), and shoulder external rotation strength (p=0.001; r=-0.620) and scapular dyskinesia. Regression analysis showed that 63.1% of scapular dyskinesia changes were related to the independent variables mentioned in this study. Conclusion It can be concluded that there is a significant relationship between shoulder rotation ROM, shoulder rotation strength, sports history, and scapular dyskinesia. Therefore, by strengthening and improving the scapular stabilizing muscles and consequently improving the shoulder rotation strength and shoulder rotation ROM in boxers, scapular dyskinesia or its intensification can be prevented.